The Influence of Social Media on Changes in Social Values among Millennials - Susiang, Maria Imelda Novita; Ghofur, Mohammad (Socious Journal, 2024)
The development of digital technology, especially social media, has significantly changed the way humans communicate and interact. The shift from face-to-face communication to virtual interaction creates a new dynamic in interpersonal relationships that prioritizes speed and efficiency. This is especially felt among the millennial generation who grow up with technological advancements. Social media has become the main platform in forming their identity, strengthening social relationships, and expressing themselves. Digital interactions through these platforms make it easier for them to engage in social movements and global issues, but they also raise concerns about the long-term impact on social skills and mental health. While social media allows for wider connectivity and participation, this engagement is often accompanied by challenges such as loss of face-to-face communication skills, identity crises, and increased anxiety and isolation. Therefore, further research is needed to understand more deeply how social media affects the interpersonal relationships and emotional well-being of this generation, as well as to formulate effective strategies in harnessing the positive potential of digital technologies, while minimizing the negative impacts that arise.